Luxury winery estates - Datz, Christian (teNeues, 2007)
This eye-catching tome takes us inside the rarefied world of high-end wineries. Spanning a variety of architectural styles, these estates are all distinguished by their luxury. And, with a pace dictated by the seasons, they are restful respites from the world outside. We?re privileged to survey a wide array of elegantly appointed living quarters?from sumptuous reception rooms to more informal settings. We get a peek at the vineyards and wine cellars, and each estate features pictures of the wine grower and their individual wine labels. ? A chance to explore the astonishing interiors of fine wineries ? Ideal for all wine lovers and those fascinated by the venerable wine trade.